Incidence of Chronic Wounds Infections in Kaduna, Nigeria - Akanni, I.O; Bolaji, R.O; Onaolapo, J.A; Igwe, J.C; Udobi, C.E; Oladipo, O.D (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Wound infection is a common complication affecting wound healing with a variety of organisms co-existing thereby predisposing affected individuals to different degrees of morbidity, severe pain, prolonged hospitalizations, increased cost of healthcare, loss of limbs and mortality. This study determined the incidence and types of bacteria infecting chronic wounds in Kaduna, Nigeria. A total of 150 wound samples were collected from December 2020-November 2021. Bacterial isolation and identification were carried out using standard culturing methods. Demographic data of patients, causes and age of wounds were obtained from medical records. Gender distribution showed male 103 (68.7%) and female 47 (31.3%) giving a male to female ratio of 2.19:1. An isolation rate of 137 (91.3%) obtained showed Staphylococcus species as most predominant 102 (60.7%) and Escherichia coli 24 (14.3%) as most frequent of Gram-negative species. Others were Proteus spp. 22 (13.1%), Klebsiella spp. 10 (5.9%), and Pseudomonas spp. 10 (5.9%). Age group 30-45 years were most affected by chronic wound infections. Wounds aged 6-24 weeks were most frequently infected. Accident wounds were the most common (37.2%) followed by diabetic foot ulcers (20.0%). Chronic wounds consist of a huge diversity of microorganisms thus requiring constant and appropriate diagnosis for quality of care.